Ecological niche overlap of two allopatric karst-adapted tiger geckos (Goniurosaurus) from northern Vietnam: microhabitat use and implications for conservation. Issue 37 (18th October 2022) - Ngo, Hai Ngoc; Nguyen, Huy Quoc; Tien, Phan Quang; Tran, Hieu Minh; Nguyen, Truong Quang; van Schingen-Khan, Mona; Ziegler, Thomas
ABSTRACT: Anthropogenic pressures have caused a substantial decline of global biodiversity and have been further reported to strongly affect the ecological performance of species in their habitat, especially reptiles. Understanding the ecology of species and how species respond to habitat alterations is basic knowledge needed to develop conservation programmes and address issues of biodiversity loss. All five species of tiger geckos ( Goniurosaurus ) in Vietnam are known to be threatened by extinction due to anthropogenic impacts such as habitat degradation and harvesting for the international pet trade. However, conservation actions have only been initiated for the better-studied species. This study provides detailed basic data on microhabitat use of two allopatric sister species, namely Goniurosaurus huuliensis and G. luii . In total, 145 geckos (including 59 records of G. huuliensis and 86 records of G. luii ) were observed during field surveys. All Goniurosaurus individuals were mostly recorded in the forest on karst formations, covered with evergreen broad-leaved woody trees, intermixed with ferns, shrubs and vines. Microhabitats of the two species were relatively similar in other traits, such as high vegetation coverage, high humidity, stable ambient temperature and dry-rock substrates. A multiple factor analysis supported that the ecological niche spaces of the two species highly overlap, even though their distribution ranges are geographically separated. We further found no intraspecific niche segregation in both species. The present data provide baseline knowledge for both in situ and ex situ conservation measures to protect species in the genus Goniurosaurus .